PEMANFAATAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SD NEGERI 2 TATAARAN - Sumilat, Juliana Margareta (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to determine whether the use of interactive math learning media can improve student learning outcomes in SD Negeri 2 Tataaran. This research was conducted using PTK design model of Kemmis Taggart research. The study was conducted in SD Negeri 2 Tataaran for 6 Months, from April to September 2017. Learning result data were obtained from the test result score. Data learning outcomes are analyzed by looking at the completeness of learning outcomes. Learning is said to have been completed if at least 75% of students have experienced completeness, and each student is said to be complete if it has a minimum learning value of 70. The results of research have shown that the use of interactive learning media can increase the math and motivation of learners, resulting in increased results student learning. This can be seen from the achievement of the research in the cycle 1 classical completeness of 70.83% increased in the second cycle of 100%, while the achievement of learning achievement in cycle 1 was 71.7% increased in the second cycle to 77.7%, thus concluded the use of interactive math learning media can improve student learning outcomes in SD Negeri 2 Tataaaran. The implications of this study indicate that when teachers use technology in learning in SD that is interactive learning media can improve the spirit and motivation learners learn that leads to increased achievement of learning outcomes.